The Influence Of Corporate Disclosure: Corporate Governance, Intellectual Capital, Asset Utilization, And Financial Performance On Corporate Value In Indonesia - Octa Naafi’ Sutantri; Agung Dinarjito (PT WIM Solusi Prima, 2023)
This study aimed to determine the influence of corporate governance, intellectual capital, asset utilization, and financial performance on corporate value. This study was quantitative research. The population of this research was manufacturing companies listed on Indonesia Stock Exchange in 2015-2019. This research used data panel with a fixed-effect model. The first model of this study showed that intellectual capital disclosure, asset utilization and financial performance had a positive impact on the corporate value which tested using Tobin’s Q. Corporate governance had a negative impact on Tobin’s Q. Meanwhile, different results were obtained from corporate value which tested using PBV. The second model of this study showed that only intellectual capital disclosure and financial performance had a positive impact on PBV. However, corporate governance and asset utilization had no impact on PBV. This research can be used as a reference for investors, companies, and financial service authorities in Indonesia to obtain higher relevance of disclosure on financial report.